Practice patterns, counseling and promotion of physical activity by sports medicine physicians. Issue 2 (February 2017) - Pojednic, Rachele M.; Polak, Rani; Arnstein, Fred; Kennedy, Mary A.; Bantham, Amy; Phillips, Edward M.
Abstract: Objectives: This study examined sports medicine physicians with an established interest in physical activity to investigate attitudes surrounding exercise, physical activity and patient-counseling behavior. The degree to which physicians' personal knowledge of physical activity and related resources, involvement with common activities, and perceived barriers were assessed. Design: An internet survey was designed in four domains: (1) counseling behavior, (2) tools and resources, (3) appropriateness of common physical activities for patients and (4) barriers. Methods: The survey was sent to 3570 members of two electronic mailing lists - Institute of Lifestyle Medicine, Boston, MA and The American College of Sports Medicine. Surveys were emailed during 2011–2012 and analyzed in 2013–2014. Each survey contained 39 questions. Results: The response rate of the surveys was 16%. Of 412 physicians, 74% regularly recommended physical activity, 66% talked about exercise with patients, and 49% included as a vital sign. Only 26% of physicians provided a written exercise prescription. ACSM's Exercise is Medicine® (37%) was the most popular resource. Walking, followed by aerobic activity, strength training and cycling were the most recommended forms of activity and were associated with physicians' personal experiences. The most potent inhibitor was time. Conclusions: Physicians with an interest in exercise and physical activity recognize the importance of recommending and counseling patients on exercise and physical activity. Physician counseling was associated with personal familiarity with physical activity. Increasing knowledge and experience with exercise, physical activity and counseling behavior is an important component to encourage physical activity assessment and promotion by sports medicine physicians.